Challenges and Opportunities of Intraoperative 3D Ultrasound With Neuronavigation in Relation to Intraoperative MRI - Bastos, Dhiego Chaves De Almeida; Juvekar, Parikshit; Tie, Yanmei; Jowkar, Nick; Pieper, Steve; Wells, Willam M.; Bi, Wenya Linda; Golby, Alexandra; Frisken, Sarah; Kapur, Tina (Frontiers in Oncology, 2021)
Introduction: Neuronavigation greatly improves the surgeon’s ability to approach, assess and operate on brain tumors, but tends to lose its accuracy as the surgery progresses and substantial brain shift and deformation occurs. iMRI can partially address this problem but is resource intensive and workflow disruptive. iUS provides real-time information that can be used to update neuronavigation and provide real-time information regarding the resection progress. We describe the intraoperative use of 3DiUS in relation to iMRI, and discuss the challenges and opportunities in its use in neurosurgical practice. Methods: We performed a retrospective evaluation of patients who underwent image-guided brain tumor resection in which both 3DiUS and iMRI were used. The study was conducted between June and December 2020.For each patient, three or more 3DiUS images were acquired during the procedure, and one iMRI was acquired towards the end. The iUS images included an extradural ultrasound sweep acquired before dural incision,a post-dural opening iUS, and a third iUS acquired immediately before the iMRI acquisition. iUS and preoperative MRI were compared to evaluate the ability of iUS to visualize tumor boundaries and critical anatomic landmarks; iUS-3 and iMRI were compared to evaluate the ability of iUS for predicting residual tumor. Results: 23 patients were included in this study. Fifteen patients had tumors located in eloquent or near eloquent brain regions, the majority of patients had low grade gliomas (11), GTR was achieved in 12 patients, postoperative temporary deficits were observed in five patients. In twenty-two iUS was able to define tumor location, tumor margins, and was able to indicate relevant landmarks for orientation and guidance. In sixteen cases, white matter fiber tracts computed from preoperative dMRI were overlaid on the iUS images. In nineteen patients, the EOR was predicted by iUS and confirmed by iMRI.The remaining four patients where iUS was not able to evaluate the presence or absence of residual tumor were recurrent cases with a previous surgical cavity that hindered good contact between the US probe and the brain surface. Conclusion: This recent experience at our institution illustrates the practical benefits, challenges, and opportunities of 3DiUS in relation to iMRI.